Children without language : from dysphasia to autism - Danon-Boileau, Laurent, 1946- (New York : Oxford University Press, 2006)
Communication and language disorders are often considered from one particular point of view - either psychological or neurological. Danon-Boileau argues that this is a serious mistake. He emphasizes that a child's trouble can stem from a variety of causes: neurological problems similar to those of aphasia, cognitive impairments, and psychological disorders, and, thus, the interaction of these elements needs to be taken into account. In precise case studies, Danon-Boileau describes the situations he has confronted and traces the causes of changes in the child when they happen. Combining linguistic, cognitive, and psycho-analytic approaches, "Children without Language" provides a unique perspective on speech and communication disorders in children and will be an essential volume for speech therapists, developmental psychologists, linguistics scholars and anyone wishing to reflect seriously on why we speak and how communication occurs
Which children are we talking about? -- Communication disorders and language disorders: rough definitions -- Communication disorder and its signs -- Engagement with language -- Principles of therapy -- Joint attention -- From communication to language -- Some cases -- Ahlem, or painful transparency -- Lanny, or the silence of the mad child -- Louis, or shared monologue -- Simon and the magic dictation -- Charles, or paradoxical communication -- Theoretical foundations -- Language and symbolization -- From sense to sound and vice versa -- Cognitive implications -- Why do some children not communicate?
Translated from the French.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Language disorders in children; Communicative disorders in children; Children; Infants; Specific language impairment in children; Aphasia; Language Development Disorders; Communication Disorders; Child; Infant; Troubles du langage chez l'enfant.; Troubles de la communication chez l'enfant.; Enfants; Nourrissons; Troubles développementaux du langage; Enfance; children (people by age group); infants; childhood; MEDICAL -- Pediatrics; HEALTH & FITNESS -- Children's Health; Infants; Children; Communicative disorders in children; Language disorders in children